Formulasi dan Uji Stabilitas Ekstrak Biji Kopi Arabika (Coffea arabica L.) sebagai Pewarna alami pada Cream Eye Brow - Chikita Inaku; Febrianti Putri Ika (An-Najat, 2025)
Arabica coffee contains caffeine, polysaccharides, chlorogenic acid, and triglycerides. Coffee can be usedfor body treatment; therefore, coffee can provide various benefits that can be used in the world ofskin beauty. Coffee is also used to relieve irritation, pmtect the skin, and fight the effects of sun exposure andfree radicals. The secondary metabolite compounds of the flavonoid group that play a role in changing the color ofnatural indicators are anthocyanins. The aim ofthis research is to determine whether Arabica coffee bean extract (Coffea arabica L.) can be formulated in theform ofan eyebrow cream dosageform that is physically and chemically stable. Experimental research method. Eyebrow cream preparations were made in each formula with concentrations of 10%, 15%, and 20%; the negative contpvl used Arabica Coffee Bean Extract (Coffea arabica L). The results of the evaluation of eyebrow cream preparations in the organoleptic, homogeneity, pH, spreadability, adhesion, and irritation tests did not indicate physical or chemical changes. Anthocvanin testfor Arabica Coffee Bean Extract (Coffea arabica L.) using a qualitative test with 2N HCL and 2N NaOH shows a reddish color that changes to blue or green, which indicates the presence of anthocyanin in the sample.